Transnational Korean Television: Cultural Storytelling and Digital Audiences - Ju, Hyejung (Transnational Communication and Critical/Cultural Studies, 2020)
Transnational Korean Television: Cultural Storytelling and Digital Audience provides previously absent analyses of Korean TV dramas' transnational influences, peculiar production features, distribution, and consumption to enrich the contextual understanding of Korean TV's transcultural mobility. Even as academic discussions about the Korean Wave have heated up, Korean television studies from transnational viewpoints often lack in-depth analysis and overlook the recently extended flow of Korean television beyond Asia. This book illustrates the ecology of Korean television along with the Korean Wave for the past two decades in order to showcase Korean TV dramas' international mobility and its constant expansion with the different Western television and their audiences. Korean TV dramas' mobility in crossing borders has been seen in both transnational and transcultural flows, and the book opens up the potential to observe the constant flow of Korean television content in new places, peoples, manners, and platforms around the world. Scholars of media studies, communication, cultural studies, and Asian studies will find this book especially useful.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Shifts in Korean Television Music Programmes: Democratization, Transnationalization, Digitalization - Jung, Sun (Television Histories in Asia: Issues and Contexts, 2015)
Korea was the fifteenth country in the world to start television broadcasting when it first launched in Seoul in 1956. Since then, the structure, content and policies concerning Korean television have continuously transformed, due largely to changing contextual circumstances such as wide-ranging socio-political democratization and the rise of the neoliberal global economic system and digital technologies. Up until the 1980s, the oligopolistic structure of the two public broadcasting networks  – Korean Broadcasting System (KBS) and Munhwa Broadcasting Corporation (MBC)  – dominated the broadcasting market. However the landscape has dramatically changed since the early 1990s, with 11 newly launched commercial terrestrial broadcasting channels (including Seoul Broadcasting System (SBS) in December 1991) and 153 cable channels when the multichannel television era began (Jin 2005 : 1). A digital satellite television system called Skylife was launched in March 2002, and airs 176 channels at the time of writing. Such changes stem from the shift in the domestic political climate where liberalization and privatization were promoted in assertively practiced neoliberal reform movement in the early 1980s, as well as changes in the global cultural industry environments based largely on globalization and the development of digital technologies. This chapter explores democratization, transnationalization and digitalization, three active factors within Korean television broadcasting by analysing changes and shifts in popular music programmes.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); _Nettoyé

Dramatizing the Nation: Television, History and the Construction of Singaporean Identity - Tay, Jinna (Television Histories in Asia: Issues and Contexts, 2015)
Television dramas, both serials and series, have been a long-term recruiter of large-scale national audiences for television broadcasters as they are potentially able to speak to their audience in affective and imaginative ways (Chan 2011 ; Sun and Gorfi nkel 2014). Usually it is the locally produced drama that resonates most with a national audience, the familiarity of the setting and context often carrying signifi cant implications for social and sometimes political life (Blandford et al. 2011 , Chan 2011 ). These television texts can pick up on popular strands of discourses in the public sphere and succeed in establishing a form of dialogue with audiences; in the instances examined in this chapter, this dialogue is about the formation of national identities or citizenships. There is good reason, then, for broadcasters and governments to attempt to use television drama to educate and persuade, although Sugg and Power ( 2011 : 26-7), long-term drama producers at the BBC World Service Trust, warn that for dramas to succeed in this manner, they first have to be entertaining, otherwise they are unlikely to generate an audience in the fi rst place. Audiences are not easily fooled and can sniff out the difference between being entertained and being preached at in a didactic way. This chapter deals with a period in the history of Singapore where television historical drama played a signifi cant role in creating a national past upon which the promotion of a distinctive national identity might be based. In addition to a consideration of a selection of drama series themselves, the chapter draws upon interviews where viewers are encouraged to share their memories of these dramas, and the part they played in the construction of a Singaporean identity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Let the Contests Begin! ‘Singapore Slings’ into Action: Singapore in the Global Television Format Business - Lim, Tania (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Why is the hit Singapore edition of Who Wants To Be A Millionaire? must-see TV?1. Watch it so that you can hold the ‘hottest topic’ with your friends. 2. So you can be encouraged by the courage of some contestants who are bold enough to brave national TV when apparently they have not read enough. 3. So you can judge for yourself if you are bold (and knowledgeable) enough to brave national TV for your possible 1st million. 4. So you can call the number on screen and make your 1st million. 5. Finally, watch it to see for yourself that Singaporeans are not as well read and as globalized as we all think we are.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves - Çetin, Berfin Emre (Cambridge Scholars Publisher, 2015)
The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves explores the representation and reception of nationalism and masculinity in Turkey through an examination of the popular television serial, Valley of the Wolves which has been aired on Turkish television since 2003. This detailed examination of the show demonstrates a particular discourse of nationalism, namely the Turkish Islam synthesis embedded in a gender-specific regime in which the paramilitary hero is placed at the centre. The study draws on thirty-seven in-depth interviews with viewers of the programme from different social backgrounds. These viewers read the serial from various perspectives in the light of their gendered experiences, suggesting that the relationship between text and audience is not necessarily predetermined by the former, but is rather constructed through an interdiscursive process. The book also examines the pleasures of the “contesting” readers of Valley of the Wolves, drawing on the audience interviews, and argues that critical approaches to a particular media text do not present a barrier to audience pleasures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Pretty Liar: Television, Language, and Gender in Wartime Lebanon - Khazaal, Natalie (Syracuse University Press, 2018)
"Pretty Liar" explores the rise of language and gender politics on Lebanese television to tell the untold story of the co-evolution of Lebanese television and its audiences and how the civil war of 1975-1991 affected that co-evolution. The shift in public interest in television has been widely acknowledged and interpreted within an institutional context as a victory of the neo-liberal entrepreneurship of a new, agile brand over the government inefficiency of Lebanon's national station, Télé Liban. Yet, the role of the Lebanese Civil War in reshaping national television and broadcasting in Arab media following the emergence of the Lebanese Broadcasting Company in 1985 has been unexplored. Based on empirical data and grounded in theory by Arab and global researchers, "Pretty Liar" offers textual analyses of five Lebanese fictional series, three major and several additional periodicals, and nine literary works, and provides context from unscripted interviews with television administrators, anchors, actors, and freelance contributors, print journalists, and audience members. Khazaal seeks to offer new insight into how entertainment television became a site for politics and political resistance, feminism, and the cradle for post-war Lebanon due to the shift in practices and standards of legitimacy. The history of television in Lebanon is not merely the history of technology and business, Khazaal argues, but rather the history of a people and their continuing quest for a responsive television even during times of civil unrest.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Liban (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Women, Television and Everyday Life in Korea: Journeys of Hope - Kim, Youna (Taylor & Francis Group, 2006)
Fusing audience research and ethnography, the book presents a compelling account of women's changing lives and identities in relation to the impact of the most popular media culture in everyday life: television. Within the historically-specific social conditions of Korean modernity, Youna Kim analyzes how Korean women of varying age and class group cope with the new environment of changing economical structure and social relations. The book argues that television is an important resource for women, stimulating them to research their own lives and identities. Youna Kim reveals Korean women as creative, energetic and critical audiences in their responses to evolving modernity and the impact of the West. Based on original empirical research, the book explores the hopes, aspirations, frustrations and dilemmas of Korean women as they try to cope with life beyond traditional grounds. Going beyond the traditional Anglo-American view of media and culture, this text will appeal to students and scholars of both Korean area studies and media and communications studies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); France (lieu de production du savoir); _Nettoyé

Watching Si Doel: Television, Language and Identity in Contemporary Indonesia - Loven, Klarijn (BRILL, 2008)
While television in today's world increasingly displays a global character, national television systems are still firmly rooted in a specific locality. But in what ways does this locality actually shape the content and performance of national television? What is the significance of local cultures and local languages in these processes of mediation? And how do the local, the national, and the global intersect in discourses of and discourse on television? Taking a critical discourse analysis perspective, Watching Si Doel investigates these and related questions in the context of contemporary Indonesia. Starting from the nationwide popularity of the local television serial Si Doel Anak Sekolahan ("Educated Doel"), it examines the various ways in which the national government, Indonesian television producers, and local audiences shape, interpret, and struggle over the meaning of the phrase 'national television'. In doing so, the book explores what Indonesian television at the turn of the century sounds and looks like--and, significantly, ought to sound and look like--according to those who create and control television and those who watch and interpret it. While providing insight into the production, nature, and reception of television discourse in general, this book particularly seeks to clarify the relationship between television, language, and power in late New Order and post-Soeharto Indonesia.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; Indonésie (corpus analysé); Pays-Bas (lieu de production du savoir); _Nettoyé

Global Conflicts, Episodic Framing and Attitude Change Towards the Israeli-Palestinian Conflict - Kampf, Ronit (Gamevironments, 2017)
This study compared the effects of episodic framing of the Checkpoint scenario and the Military Raid scenario in Global Conflicts (2010), a computerized simulation of the Israeli-Palestinian conflict, on developing impartial attitudes towards this conflict. The former presents a more human, individual and personal framing of the conflict than does the latter. Two hundred and ten Israeli-Jewish and Palestinian undergraduate students participated in the experiment. They filled in questionnaires measuring attitudes towards the Israeli-Palestinian conflict before and after playing the scenarios. Results suggested that participants playing the Checkpoint scenario became more impartial toward the Israeli-Palestinian conflict, unlike those playing the Military Raid scenario. The results show that computerized simulations of the Israeli-Palestinian conflict can be used for attitude change intervention, but the framing of the story in the game may be crucial in determining whether the players become impartial regarding the situation or not.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; _Nettoyé

First Person Encounters #1: A Game Studies India Adda Podcast - Game Studies India Adda (2020)
The First Podcast in a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

War Games: Memory, Militarism and the Subject of Play - Hammond, Philip; Pötzsch, Holger (Bloomsbury Publishing USA, 2019)
Many of today's most commercially successful videogames, from Call of Duty to Company of Heroes, are war-themed titles that play out in what are framed as authentic real-world settings inspired by recent news headlines or drawn from history. While such games are marketed as authentic representations of war, they often provide a selective form of realism that eschews problematic, yet salient aspects of war. In addition, changes in the way Western states wage and frame actual wars makes contemporary conflicts increasingly resemble videogames when perceived from the vantage point of Western audiences.This interdisciplinary volume brings together scholars from games studies, media and cultural studies, politics and international relations, and related fields to examine the complex relationships between military-themed videogames and real-world conflict, and to consider how videogames might deal with history, memory, and conflict in alternative ways. It asks: What is the role of videogames in the formation and negotiation of cultural memory of past wars? How do game narratives and designs position the gaming subject in relation to history, war and militarism? And how far do critical, anti-war/peace games offer an alternative or challenge to mainstream commercial titles?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Gaming at the Edge: Sexuality and Gender at the Margins of Gamer Culture - Shaw, Adrienne (University of Minnesota Press, 2015)
Video games have long been seen as the exclusive territory of young, heterosexual white males. In a media landscape dominated by such gamers, players who do not fit this mold, including women, people of color, and LGBT people, are often brutalized in forums and in public channels in online play. Discussion of representation of such groups in games has frequently been limited and cursory. In contrast, Gaming at the Edge builds on feminist, queer, and postcolonial theories of identity and draws on qualitative audience research methods to make sense of how representation comes to matter. In Gaming at the Edge, Adrienne Shaw argues that video game players experience race, gender, and sexuality concurrently. She asks: How do players identify with characters? How do they separate identification and interactivity? What is the role of fantasy in representation? What is the importance of understanding market logic? In addressing these questions Shaw reveals how representation comes to matter to participants and offers a perceptive consideration of the high stakes in politics of representation debates. Putting forth a framework for talking about representation, difference, and diversity in an era in which user-generated content, individualized media consumption, and the blurring of producer/consumer roles has lessened the utility of traditional models of media representation analysis, Shaw finds new insight on the edge of media consumption with the invisible, marginalized gamers who are surprising in both their numbers and their influence in mainstream gamer culture.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Gaming Cultures and Place in Asia-Pacific - Hjorth, Larissa; Chan, Dean (Routledge studies in new media and cyberculture, 2009)
This collection explores the relationship between digital gaming and its cultural context by focusing on the burgeoning Asia-Pacific region. Encompassing key locations for global gaming production and consumption such as Japan, China, and South Korea, as well as increasingly significant sites including Australia and Singapore, the region provides divergent examples of the role of gaming as a socio-cultural phenomenon. Drawing from micro ethnographic studies of specific games and gaming locales to macro political economy analyses of techno-nationalisms and trans-cultural flows, this collection provides an interdisciplinary model for thinking through the politics of gaming production, representation, and consumption in the region.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Playing at Being Mobile: Gaming and Cute Culture in South Korea - Hjorth, Larissa (Fibreculture Journal, 2006)
This paper is based on ongoing research into the gendered use of mobile convergent media in the Asia-Pacific region. In particular, what role does the cute have and how does it correlate with types of consumption? As a region, the Asia-Pacific is marked by diverse penetration rates, subject to local cultural and socio-economic nuances. Two defining locations - Seoul (South Korea) and Tokyo (Japan) - are seen as both mobile centres and gaming centres which the world looks towards as examples of the future-in-the-present. Unlike Japan, which pioneered the keitai (mobile) IT revolution with devices such as i-mode, South Korea has become a centre for mobile DMB (Digital Multimedia Broadband) with the successful implementation of TV mobile phones (TU mobile) in 2005. One of the key features of mobile media technologies is the attempt by the industry to find the next killer application . One such application is the possibility of online multiplayer games accessed through mobile (broadband) telephonic devices such as MMO golf RPG Shot Online (a golf game for mobile phones). Amongst this frenzy of trend spotting and stargazing, Seoul as a mobile broadband and gaming centre provides a curious case study for the social and cultural intricacies informing the rise of gaming as an everyday practice for many Koreans.This article begins by outlining the game play and technoculture particular to South Korea and then explores the phenomenon of Kart Rider in South Korean gaming cultures - and its perception/ reception outside Korea - to sketch some of the issues at stake in playing it cute (particularly in the form of cute avatars), consuming Korea and the endurance of co-present communities. In particular, it contemplates the implications of current emerging online mobile gaming genres such as so-called female games such as the cute' Kart Rider in order to think about changing modes of game play and attendant social spaces.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; _Nettoyé